Goals for Teaching English as an International Language for Saudi Students in Sciences and Humanities College: A Framework for Teaching English as an International Language in Sciences and Humanities College (Journal of Advances and Scholarly Researches in Allied Education, 2018)
It can be said that English is dominant as a language for interaction, education, medicine, conferences, and the second language in some countries. Consequently, teaching English as the international language (TEIL) becomes a demand for all the current generation and in the future. For this paper, it is important to present the characteristics of the environment and the resources for the students and the teachers. Sciences and Humanities College is equipped with newer technologies such as computers, smart boards, projectors, the Internet, portal. Here I will introduce some goals that are sitting by the authorities for teaching English in Sciences and Humanities College. Teaching English as an international language is a new paradigm, and it should be planned coherently to meet the global communication demands. Therefore, Celce-Murcia’s framework of communicative competence can be useful to determine my goals. It contains linguistics, sociocultural, formulaic, interactional, strategic, and discourse competencies.